Figurative Language in The Song Lyrics of Passenger’s Album “All the Little Lights” - Agus Krisna Permana, I Gede; Rajeg, I Made (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p18, 2018)
Figurative language can appear in various types and the meaning may not be determined by its components. This study aims to identify and analyze the meaning of figurative language found in the song lyrics “Passenger's album all the little lights”. There are two theories used in this study. The first is the theory of figurative language proposed by Knickerbocker and Reninger, and the second is the theory of meaning by Leech as the supporting theory. The data in this study were directly taken from Passenger’s fourth album. The album consists of twelve songs. They were collected by documentation method and note taking technique. The collected data were analyzed  using qualitative and descriptive method. This study applied informal method to present the analysis. The result of this study shows that there are nine types of figurative language found in song lyrics. They were allusion, simile, metaphor, irony, personification, hyperbole, dead metaphor, metonymy, and paradox. Most of the figurative expressions found in those songs were similes. Four out of seven types of meaning used in those lyrics in order to understand the figurative meaning in the song lyrics; they were connotative meaning, conceptual meaning, affective meaning, and collocative meaning. All the songs which are analyzed have the main theme about life and love .